In every organization, gender stereotypes reduce organizational efficiency and waste productive energy: a systems thinking perspective. Issue 13 (19th April 2022) - Mella, Piero
Abstract : Purpose: Stereotypes are simplified and widely shared visions held by a social group regarding a place, object, event or recognizable set of people united by certain characteristics or qualities. They are "dangerous" mental models because they are widely disseminated, devious and capable of acting even unconsciously in individuals, social groups and organizations altering the rationality of assessments and choices and producing discrimination and prejudice. Stereotypes acritically extend from a characteristic of a significant percentage of a category to the totality of individuals. The process of generalization triggered by a stereotype produces the error of discrimination and prejudice. There are numerous forms of stereotypes, but this study takes into account gender stereotypes because they act pervasively, often subtly, to reduce "productivity". People who are aware of being discriminated perceive an unsatisfactory fulfillment of their motivations, which reduces their incentive to improve their performance. Since productivity measures the efficient use of energy from working in production processes, the author believes that wherever gender stereotypes are at play, there is a productive "waste of energy", an inefficiency in work activity with harmful effects for organizations of all kinds, including families. Design/methodology/approach: The work aims to demonstrate that wherever gender stereotypes are at play, a "waste of energy" manifests itself in terms of productivity, representing an inefficiency in work activity with harmful effects for organizations of all kinds, including families. To describe the negative effects stereotypes produce in organizations, some models are presented based on the methods and language of systems thinking. These models, although typically qualitative, are capable of exploring the most accepted theories in the literature: tournament theory, the Pygmalion effect, the Galatea effect, self-fulfilling prophecies, the Queen bee syndrome, the role congruency theory, the glass ceiling theory ("think manager, think male" and "family responsibilities wall"). The paper follows a predominantly organizational and corporate approach, although the copious literature on stereotypes belongs largely to the area of social psychology and organization studies. Findings: The paper does not consider the psychological origin of stereotypes but highlights their use as routines-shortcuts for evaluations and decisions demonstrating that, when adopted in social systems and within organisations, stereotypes produce different forms of discrimination: in social rights, in work, in careers and in access to levels of education and public services, reducing performance and limit potential. The paper also examines some ways gender and culture stereotypes can be opposed, presenting a change management strategy and some concrete solutions proposed by the process–structure–culture model for social change (PSC model). Research limitations/implications: The main limitation of the work is that it focuses on gender stereotypes, choosing not to consider the "intersection effect" of these with other stereotypes: racial stereotypes, religious stereotypes, color stereotypes, age stereotypes, sex and sexual orientation stereotypes, and many others, whose joint action can cause serious inefficiencies in organizational work. Practical implications: As stereotypes are a component of social culture and are handed down, by use and example, from generation to generation, the maintenance over time of stereotypes used by individuals to evaluate, judge and act can be seen as an effect of the typical action of a combinatory system of diffusion, which can operate for a long time if not effectively opposed. Il PSC model indicates the strategy for carrying out this opposition. Social implications: With regard to gender stereotypes, it should be emphasized that in organizations and social systems, "gender diversity" should be considered an opportunity and not as a discriminating factor and thus encouraged by avoiding harmful discrimination. In fact, this diversity, precisely because of the distinctive characteristics individuals possess regardless of gender, can benefit the organization and lead to an increase in organizational and social performance. The United Nations 2030 Agenda for Sustainable Development (2020) Goal 5: Achieving gender equality and empowering all women and girls is examined in this context. Originality/value: This study views the action of gender stereotypes as especially harmful "mental models", highlighting the distortions they cause in the allocation of productive energy in society, groups and organizations. The paper follows a predominantly organizational and corporate approach, although the copious literature on stereotypes belongs largely to the area of social psychology. Using the "logic" and "language" of systems thinking, theories and models that describe and interpret the distorting effects of organizational choices based on stereotypes rather than rational analysis are highlighted. The action of stereotypes and their persistence over time can also be described using combinatory systems theory. With this paper, the author hopes that by acting on the three wheels of change highlighted by the PSC model, through legal provisions, control tools and actions on the culture operated by educational and social aggregative institutions, it should not be impossible to change the prevailing culture so that it becomes aware of the harmful influence of gender stereotypes and other discriminatory mental models and come to reject them. The author hopes this paper will help to understand the need to make this change.